Reducing optimism bias in the driver's seat: Comparing two interventions. (April 2021) - Cutello, Clara Alida; Walsh, Clare; Hanoch, Yaniv; Hellier, Elizabeth
Highlights: This is one of the few studies to assess two different interventions to reduce optimism bias in young novice drivers. The results will be of interest to a wide spectrum of academics and non-academic audiences (police, policymakers, fire and rescue services). The present results have clear implications for the design and implementation of preventive programs across the globe. The results will be of interest to the general public as well as a range of media outlets. Abstract: Optimism bias combined with sensation-seeking and risky driving have been proposed to be the main contributing factors to young drivers' involvement in road traffic collisions. The present study aimed to evaluate how two brief interventions, one based on an unambiguous definition of "good" driving and the other on a hazard perception test, might reduce young drivers' optimism bias. One hundred and twenty-eight university students were randomly allocated to one of three groups: standard definition, hazard perception or control. Measures evaluating optimism bias were completed before and after the intervention, and questions regarding their sensation-seeking and past risk-taking tendencies were asked at follow-up. Both brief interventions reduced optimism bias levels, but hazard perception had the strongest effect. The effectiveness of the two interventions also differed across individuals depending on their sensation-seeking and past risky driving tendencies. The results provide evidence for the effectiveness of brief interventions to reduce optimism bias.